Association of Physical Fitness Indicators with Health Profile and Lifestyle of Children - TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: High physical fitness (PF) level is a significant health determinant in children and adolescents so that it is important to identify the factors affecting PF in this population. Despite available studies highlighting the relationship between PF and characteristics of children, there is still a need to uncover how the health status and lifestyle of children impact different PF indicators. Thus, the purpose of this study is to investigate the relationship between physical fitness, and the health profile and lifestyle of children. Methods: This study was conducted with 110 (58 girls; age 11.85 +/- 0.35) adolescents between February and March 2020. The preditors of PF which were gender, body mass index, physical activity level (PAL) measured via Physical Activity Questionnaire (PAQ), motivation measured via Participation Motivation Questionnaire (PMQ), sleep time, and tablet usage time regressed against PF related outcome measured using 6 Minutes Walk test (6MWT), T-Test, vertical jump test and broad jump test (BJT). Results: There were significant associations between T-test performance, and gender, BMI (being obese), and PAL. PAL and gender were also significant predictors for 6MWT and BJT respectively. PF was not significantly associated with motivation, sleep, and table usage time. A high level of physical activity, being male, and low BMI score resulted in better PF performance. Conclusion: The health profile and lifestyle of adolescents may estimate the significant proportion of variabilities observed in physical fitness levels in adolescents.
Keywords: Physical Fitness; Adolescent; Physical Activity; Healthy Lifestyle; 6-MINUTE WALK TEST; SEDENTARY BEHAVIOR; SCREEN-TIME; AGED 6; CHILDHOOD; YOUTH; ADOLESCENTS; VALUES; GUIDELINES; ADULTHOOD